LOW-DEGREE PARTIAL MELTING TRENDS RECORDED IN UPPER MANTLE MINERALS - Schiano P.; Bourdon B.; Clocchiatti R.; Massare D.; Varela M.E.; Bottinga Y. (My University, 1998)
The study of glass inclusions inside mantle minerals provides direct information about the chemistry of naturally occurring mantle-derived melts and the fine-scale complexity of the melting process responsible for their genesis. Minerals in a spinel lherzolite nodule from Grande Comore island contain glass inclusions which, after homogenization by heating, exhibit a continuous suite of chemical compositions clearly distinct from that of the host basanitic lava. The compositions range from silicic, with nepheline-olivine normative, 64 wt% SiO2 and 11 wt% alkali oxides, to almost basaltic, with quartz normative, 50 wt% SiO2 and 1-2 wt% alkali oxides. Within a single mineral phase, olivine, the inferred primary melt composition varies from 54 to 64 wt% SiO2 for MgO content ranging from 8 to 0.8 wt%. An experimental study of the glass and fluid inclusions indicates that trapped melts represent liquids that are in equilibrium with their host phases at moderate temperature and pressure (T~1230°C and P~1.0 Gpa for melts trapped in olivine). Quantitative modelling of the compositional trends defined in the suite shows that all of the glasses are part of a cogenetic set of melts formed by fractional melting of spinel lherzolite, with F varying between 0.2 and 5%. The initial highly silicic, alkali-rich melts preserved in Mg-rich olivine become richer in FeO, MgO, CaO and Cr2O3 and poorer in SiO2, K2O, Na2O, Al2O3 and Cl with increasing melt fractions, evolving toward the basaltic melts found in clinopyroxene. These results confirm the connection between glass inclusions inside mantle minerals and partial mantle melts, and indicate that primary melts with SiO2 >60 wt%, alkali oxides >11%, FeO <1 wt% and mgo <1 are generated during incipient melting of spinel peridotite. the composition primary melts is inferred to be dependent on pressure, reflect both speciation dissolved co2 and the effect of alkali oxides on the silica activity coefficient in the melt. At pressures around 1 GPa, low-degree melts are characterized by alkali and silica-rich compositions, with a limited effect of dissolved CO2 and a decreased silica activity coefficient caused by the presence of alkali oxides, whereas at higher pressures alkali oxides form complexes with carbonates and, consequently, alkali-rich silica-poor melts will be generated.
Keywords: PARTIAL MELTING; GLASS; INCLUSIONS; SPINEL LHERZOLITE